Dynamic surface tracking controller design for a constrained hypersonic vehicle based on disturbance observer. (8th May 2017) - Wang, Fang; Zou, Qin; Hua, Changchun; Zong, Qun
The tracking control problem of a flexible air-breathing hypersonic vehicle subjects to aerodynamic parameter uncertainty and input constraint is investigated by combining nonlinear disturbance observer and dynamic surface control. To design controller simply, a control-oriented model is firstly derived and divided into two subsystems, velocity subsystem and altitude subsystem based on the engineering backgrounds of flexible air-breathing hypersonic vehicle. In every subsystem, compounded disturbances are included to consider aerodynamic uncertainty and the effect of the flexible modes. Then, disturbance observer is not only used to handle the compounded disturbance but also to handle the input constraint, where the estimation error converges to a random small region through appropriately choosing the observer parameters. To sequel, the disturbance observer–based robust control scheme and the disturbance observer-based dynamic surface control scheme are developed for the velocity subsystem and altitude subsystem, respectively. Besides, novel filters are designed to alleviate the problem of "explosion of terms" induced by backstepping method. On the basis of Lyapunov stability theory, the presented control scheme can assure that tracking error converges to an arbitrarily small neighborhood around zero by rigorous theoretical analysis. At last, simulation result shows the effectiveness of the presented control method.